The burden of diabetes and use of diabetes care in humanitarian crises in low-income and middle-income countries. Issue 8 (August 2019) - Kehlenbrink, Sylvia; Smith, James; Ansbro, Éimhín; Fuhr, Daniela C; Cheung, Anson; Ratnayake, Ruwan; Boulle, Philippa; Jobanputra, Kiran; Perel, Pablo; Roberts, Bayard
Summary: Human suffering as a result of natural disasters or conflict includes death and disability from non-communicable diseases, including diabetes, which have largely been neglected in humanitarian crises. The objectives of this Series paper were to examine the evidence on the burden of diabetes, use of health services, and access to care for people with diabetes among populations affected by humanitarian crises in low-income and middle-income countries, and to identify research gaps for future studies. We reviewed the scientific literature on this topic published between 1992 and 2018. The results emphasise that the burden of diabetes in humanitarian settings is not being captured, clinical guidance is insufficient, and diabetes is not being adequately addressed. Crisis-affected populations with diabetes face enormous constraints accessing care, mainly because of high medical costs. Further research is needed to characterise the epidemiology of diabetes in humanitarian settings and to develop simplified, cost-effective models of care to improve the delivery of diabetes care during humanitarian crises.